Understanding the Proceeds of Crime Act 2002: Cash Seizure and Frontline Policing. (26th November 2012) - Cram, Frederick
Abstract Recent shifts in modes of criminal justice have precipitated a startling expansion of police powers in England and Wales (Brownlee 1998; Reiner 2007). The Proceeds of Crime Act 2002 (POCA) (as amended) is an example of a growing trend towards the use of hybrid civil‐criminal legislation. The Act can be situated within a criminal justice paradigm, often referred to as the 'new penology' of risk, or 'actuarial justice' (Feeley and Simon 1992, p.449). Part 8 provides frontline police officers with additional, extensive and far‐reaching cash seizure powers for the disruption and frustration of serious, often organised, acquisitive crime. Though laudable in its aims, the legislation is susceptible to manipulation by officers wanting to secure broader social and disciplinary objectives, often pertaining to the organisational subcultural norms of rank‐and‐file police officers. Its provisions have become part of mainstream policing powers. An exploration of the broader implications of mainstreaming the cash seizure powers into frontline policing has, therefore, become timely. In this article, I conduct such an examination, concluding by setting out an agenda for more critical research than has been undertaken to date.